2015
DOI: 10.3233/jad-142847
|View full text |Cite
|
Sign up to set email alerts
|

Serum miR-206 and miR-132 as Potential Circulating Biomarkers for Mild Cognitive Impairment

Abstract: MicroRNAs (miRNAs), a class of small, non-coding RNA molecules with gene regulatory functions, have emerged to play a critical role in the pathogenesis of a variety of diseases. Recently, circulating miRNAs have been reported as potential biomarkers for various pathologic conditions. The present study was performed to investigate the potential role of circulating miRNAs as diagnostic biomarkers for mild cognitive impairment (MCI). We collected 66 patients with MCI and 76 normal controls from our previous cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 46 publications
6
56
0
2
Order By: Relevance
“…These results preliminarily indicated that miRNA-132 might be a potential biomarker for the diagnosis of MCI. A significantly upregulated expression of miRNA-132 was reported among patients with MCI (n = 66) in comparison to their agematched controls (n = 76) [61]. Moreover, Weinberg et al, [62] assessed miRNA 132 in the frontal and inferior temporal cortex of postmortem brains of patients with MCI and normal individuals and found that miR 132 was significantly down-regulated in MCI.…”
Section: Discussionmentioning
confidence: 99%
“…These results preliminarily indicated that miRNA-132 might be a potential biomarker for the diagnosis of MCI. A significantly upregulated expression of miRNA-132 was reported among patients with MCI (n = 66) in comparison to their agematched controls (n = 76) [61]. Moreover, Weinberg et al, [62] assessed miRNA 132 in the frontal and inferior temporal cortex of postmortem brains of patients with MCI and normal individuals and found that miR 132 was significantly down-regulated in MCI.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there is a discrepancy in existing data of blood-based miRNAs in MCI patients because MCI was either considered as a dementia type/stage different than AD [22, 23, 39, 43] or MCI was assumed to represent early AD, and was included in the analysis together with probable AD as one disease group [20, 21]. Some other authors attempted to stratify the MCI group according to dementia psychological assays and PIB-PET brain imaging, but the classification omitted CSF markers and thus cannot be referred to such biochemical measures [41, 6870]. To avoid such problems, our study involved only those patients diagnosed with MCI, in which analysis of AD biomarkers in CSF indicated likelihood of early AD.…”
Section: Discussionmentioning
confidence: 99%
“…In animal models of AD, previous studies have reported an increased expression of miR-206 in brain tissue, CSF and plasma of embryonic amyloid precursor protein (APP)/presenilin 1 transgenic mice (23) and Tg2576 mice (24). Furthermore, upregulation of miR-206 has been detected in serum from patients with mild cognitive impairment (25), and in the temporal cortex of human AD brains (24). These results indicated that upregulation of miR-206 in the peripheral circulation truly reflects the alterations in the AD brain.…”
Section: A B C Dmentioning
confidence: 99%